Pengaruh Learning Demand dan Resources terhadap Burnout Mahasiswa Universitas Kristen Petra - Gerald Gerald; I Nyoman Sutapa; Prayonne Adi (Jurnal Titra, 2022)
The COVID-19 virus pandemic has spread throughout the world. This makes a lot of impact in all sectors. One of the impacts is in the education sector. Government policies are carried out to break the chain of the spread of the COVID-19 virus. Therefore, the government requires studying at home. The number of tasks that must be completed by students both individually and in groups causes a lot of burnouts. To reduce burnout, resources are needed as a buffer so that the burnout level can be reduced. Therefore, this study aims to determine the effect of learning demand with personal moderators and organization resources on burnout. This research was conducted by distributing questionnaires to 74 Industrial Engineering students at Petra Christian University. After the data was collected, the researchers analysed descriptively and to determine the effect between variables using the Structural Equation Model (SEM) method. The results of the study stated that learning demand had a significant positive effect on burnout. Personal Resources as a moderator is able to weaken the influence of learning demand on burnout. Organizational resources as moderators are not able to significantly weaken or strengthen the influence of learning demand on burnout.